2015
DOI: 10.1016/j.scitotenv.2015.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire patterns and landscape changes in Mediterranean oak woodlands

Abstract: • Transitions in Mediterranean oak woodlands (montados) were assessed; • Low spatial connectedness in montado landscape increases its vulnerability; • Changes were mostly explained by fire characteristics and spatial factors; • Large fires have a major role in transitions from montado to pioneer communities. Fire is infrequent in the oak woodlands of southern Portugal (montado) but large and severe fires affected these agro-forestry systems in [2003][2004][2005]. We hypothesised transition from forest to shrub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 112 publications
1
21
0
Order By: Relevance
“…For instance, an increase in greenhouse gas emissions is expected, which in turn favors climate warming . Moreover, increasing wildfires might cause substantial changes in the existing vegetation composition and distribution or even desertification of some areas and probably a subsequent erosion . Many Mediterranean plants are adapted to cope with fire, but some Mediterranean ecosystems may be strongly affected by wildfires .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an increase in greenhouse gas emissions is expected, which in turn favors climate warming . Moreover, increasing wildfires might cause substantial changes in the existing vegetation composition and distribution or even desertification of some areas and probably a subsequent erosion . Many Mediterranean plants are adapted to cope with fire, but some Mediterranean ecosystems may be strongly affected by wildfires .…”
Section: Discussionmentioning
confidence: 99%
“…In fact some works point out that rural residents display lower preference for wilderness landscapes than urbanites (Balling and Falk, 1982;Strumse, 1996), and according to the distribution of respondents within the clusters this result could show a contradictory trend to the one published in the literature. However, in this case, the landscapes are dominated by early-successional communities, with low density of trees resulting from low-intensity management, abandonment of farming or ecological disturbances (Gallego-Fernández et al, 2004;Guiomar et al, 2015). Thus, these patches cannot be compared with idyllic landscapes, with leafy and dense vegetation or with recreational potential.…”
Section: Diversified Appreciation Patterns For Rural Landscapementioning
confidence: 99%
“…The revived interest in agroforestry originates from an increasing amount of evidence of environmental (Palma et al 2007a(Palma et al , 2007bReisner et al, 2007;Rigueiro et al 2009;Andrianarisoa et al, 2015;Cardinael et al, 2015), social and economic benefits (Graves et al 2007;Glover et al, 2013;Mercer et al, 2014;Ranca et al, 2014) of this land use system. However, many of these systems are declining, showing high vulnerability to changes in disturbance regimes such as fire and drought (Acácio et al, 2009;Guiomar et al, 2015;Paulo et al,2016) and to pests and diseases (Hansen, 2015;Tiberi et al, 2016). Gibbons et al (2008) showed that the progressive loss of trees in agrarian landscapes has been a global pattern.…”
Section: Introductionmentioning
confidence: 99%